Lithium manganese iron phosphate material and preparation method thereof

Lithium manganese iron phosphate material was prepared by solvent thermal synthesis method and high-energy ball milling technology, combined with hot press sintering to optimize carbon coating, which solved the problems of poor conductivity and poor cycle stability in traditional processes, and achieved efficient and uniform material preparation. Improves conductivity and cyclic stability.

CN119390036AActive Publication Date: 2025-02-07HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411581359.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-07
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The traditional preparation process of lithium manganese iron phosphate material has problems such as poor conductivity, high grinding difficulty, uneven element dispersion and uneven carbon coating, resulting in unsatisfactory electrical conductivity and cyclic stability of the material.

Method used

The ferromanganese ternary metal-glycerate precursor is prepared by solvent thermal synthesis method, and combined with high-energy ball milling and hot press sintering technology to form lithium manganese ferromanganese phosphate material. This method significantly improves the conductivity and cyclic stability of the material by uniformly distributing elements and optimizing carbon coating.

Benefits of technology

It has achieved high conductivity and good cycle stability of lithium manganese iron phosphate material, improved the compaction density and electrochemical performance of the material, and has high production efficiency, and has industrial application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005123193030000121
    Figure BDA0005123193030000121
  • Figure BDA0005123193030000131
    Figure BDA0005123193030000131
Patent Text Reader

Abstract

The preparation method comprises the following steps: preparing a manganese iron M ternary metal-glycerate precursor by adopting a solvothermal synthesis method, then mixing the manganese iron M ternary metal-glycerate precursor with a phosphorus source and a lithium source, carrying out high-energy ball milling, and carrying out primary CVD-like sintering and secondary hot pressed sintering to obtain the manganese iron lithium phosphate material. According to the preparation process disclosed by the invention, the lithium manganese iron phosphate material with high compaction density and excellent conductivity and cycling stability can be obtained, the production efficiency is high, and the preparation process has industrial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery positive electrode materials, and in particular to a lithium manganese iron phosphate material and a preparation method thereof. Background Art

[0002] With the continuous development of portable electronic devices, electric vehicles and large-scale energy storage equipment markets, the performance improvement of lithium-ion batteries has become increasingly important. The positive electrode is one of the key components of lithium-ion batteries, and the performance of the positive electrode material plays a decisive role in the performance of lithium-ion batteries. Olivine-type positive electrode materials have the advantages of high safety performance and low cost. Among them, lithium iron manganese phosphate and lithium iron phosphate are both olivine-type positive electrode materials. Lithium iron phosphate materials have good safety performance and cycle stability, but their low voltage platform is difficult to meet the increasing demand for energy density; compared with lithium iron phosphate, the high voltage characteristics of manganese make lithium iron manganese phosphate have a higher voltage platform, which increases its energy density by 10% to 20% when its specific capacity is the same as that of lithium iron phosphate. In addition, lithium iron manganese phosphate takes into account the high safety, high cycle life, low cost, and environmental friendliness of lithium iron phosphate. It is one of the hot research materials for lithium-ion battery positive electrode materials.

[0003] In addition to the advantage of high voltage, the introduction of manganese also brings the problem of poor conductivity to lithium iron manganese phosphate materials. To solve this problem, the raw materials can usually be ground by a sand mill to achieve nano-sizing, shorten the lithium ion transmission path, and then supplemented with appropriate carbon coating methods, such as mixing with a carbon source and sintering at high temperature to improve the electronic conductivity of the material. However, the traditional sand milling process is difficult to achieve nano-sizing, takes a long time, and cannot achieve the effect of material nano-sizing in a short time, and the actual production process is inefficient; in addition, the problem of uniformity of raw material dispersion in the grinding method will also have a great impact on the performance of lithium iron manganese phosphate materials. The uneven dispersion of manganese and iron elements during the grinding process will not only cause distortion of the crystal structure, hinder the transmission of lithium ions, and lead to a decrease in conductivity, but also aggravate the manganese dissolution problem caused by the Jahn-Teller effect, making the cycle stability of lithium iron manganese phosphate materials worse. In addition, the traditional high-temperature sintering method has the problems of uneven carbon coating and excessive particle size of the material particles after sintering, which makes the improvement effect of the conductivity of lithium iron manganese phosphate materials less than ideal. In summary, developing a preparation process with high production efficiency and effective improvement of the conductivity of lithium manganese iron phosphate materials is of great practical significance. Summary of the invention

[0004] Based on the technical problems existing in the background technology, the present invention proposes a lithium manganese iron phosphate material and a preparation method thereof.

[0005] The present invention provides a method for preparing lithium manganese iron phosphate material, comprising the following steps:

[0006] S1. preparing a manganese iron M ternary metal-glycerate precursor by a solvothermal synthesis method, wherein M is magnesium, nickel, cobalt or aluminum;

[0007] S2, mixing the manganese iron M ternary metal-glycerate precursor with a phosphorus source and a lithium source and performing high-energy ball milling to obtain a manganese iron phosphate lithium precursor;

[0008] S3, placing the lithium iron manganese phosphate precursor in a reaction furnace, introducing a mixed gas of a carbon source gas and a protective gas, and sintering the precursor to obtain a primary sintered product;

[0009] S4, cold-pressing the primary sintered product into a shape, and then hot-pressing and sintering the product under a protective atmosphere to obtain the lithium manganese iron phosphate material.

[0010] The present invention synthesizes a ternary metal-glycerate precursor of manganese iron M by a solvent thermal method, which can achieve good uniformity of element distribution in the precursor, thereby improving the uniformity of element distribution in the lithium iron manganese phosphate material, and effectively improving the conductivity and cycle stability of the lithium iron manganese phosphate material; and because the metal-organic composite precursor synthesized by the solvent thermal method has a smaller particle size, the difficulty of the subsequent sand grinding process to reduce the particle size is significantly reduced, and the nano-sizing of the material can be achieved in a shorter time; by combining a primary CVD-like sintering and a secondary hot pressing sintering, the optimal carbon coating effect is achieved on the basis of limited carbon content, and the particle size growth of the lithium iron manganese phosphate material is effectively limited, giving the material good conductivity, and hot pressing sintering can also improve the density of the material, thereby obtaining a good compaction density level.

[0011] Preferably, in the manganese-iron-M ternary metal-glycerate precursor, the molar ratio of manganese element, iron element and M element is (0.55-0.75): (0.40-0.20): 0.05.

[0012] Preferably, the preparation step of the manganese iron M ternary metal-glycerate precursor comprises: fully dissolving manganese salt, iron salt and M metal salt in isopropanol, adding glycerol to mix evenly, and then performing a solvothermal reaction to obtain. Through the above specific solvothermal synthesis steps, the uniformity of element distribution in the precursor can be improved, thereby further improving the conductivity and cycle stability of the lithium manganese iron phosphate material.

[0013] Preferably, the manganese salt is manganese nitrate tetrahydrate, and the iron salt is ferric nitrate nonahydrate.

[0014] Preferably, the M metal salt is a nitrate of M metal.

[0015] Preferably, the ratio of the sum of the molar amounts of the manganese element in the manganese salt, the iron element in the iron salt, and the M element in the M metal salt to the molar amount of glycerol is 1:2-5.

[0016] Preferably, the temperature of the solvothermal reaction is 150-180° C. and the time is 10-20 hours. By controlling the temperature and time of the solvothermal reaction, a precursor with suitable particle size and high uniformity can be obtained, thereby further improving the conductivity and cycle stability of the lithium manganese iron phosphate material.

[0017] Preferably, in the step of preparing the manganese iron M ternary metal-glycerate precursor, glycerol is added and mixed evenly under stirring, and the stirring speed is 200-300 r / min and the time is 1-3 h.

[0018] In the preparation steps of the manganese iron M ternary metal-glycerate precursor, after the solvothermal reaction is completed, conventional post-treatment steps can also be included, such as centrifuging the product, washing and drying the precipitate; the washing process includes: rinsing with deionized water and ethanol 3-5 times in sequence; the drying temperature is 80-100°C and the time is 10-20 hours.

[0019] Preferably, in S2, the ratio of the sum of the molar amounts of manganese, iron and M in the manganese-iron-M ternary metal-glycerate precursor to the molar amount of the phosphorus source and the molar amount of the lithium in the lithium source is 1:(0.95-1.05):(1-1.1), preferably 1:1:(1.01-1.05).

[0020] Preferably, the phosphorus source is at least one of diammonium phosphate, diammonium hydrogen phosphate, ammonium phosphate, and phosphoric acid.

[0021] Preferably, the lithium source is at least one of lithium carbonate, lithium hydroxide, lithium chloride and lithium acetate.

[0022] Preferably, in S2, the rotation speed of the high energy ball mill is 300-500 r / min, and the time is 5-10 h. Controlling the conditions of high energy ball milling can make the precursor have a suitable particle size and excellent uniformity, improve the effect of carbon coating, and further improve the conductivity and cycle performance of the material.

[0023] Preferably, in S2, the high-energy ball milling is carried out in a solvent, the solvent is anhydrous ethanol, and after the ball milling is completed, the solvent is removed by drying.

[0024] Preferably, in S3, the flow rate of the mixed gas of the carbon source gas and the protective gas is 70 mL / min to 120 mL / min, and the volume ratio of the carbon source gas to the protective gas is (2 to 4): 10. Under the gas flow rate and ratio, a uniform and thin coating layer can be formed on the surface of the lithium manganese iron phosphate material, which improves the electrical conductivity while reducing the proportion of inactive carbon, which is beneficial to improving the electrical conductivity and cycle performance of the material.

[0025] Preferably, the carbon source gas is at least one of methane, ethane and propane.

[0026] Preferably, in S3, the sintering temperature is 500-600° C. and the holding time is 4-6 hours. Under the sintering conditions, the lithium manganese iron phosphate material can be formed into a phase with high particle size uniformity, which is beneficial to improving the conductivity and cycle stability of the material.

[0027] Preferably, in S4, the sintering temperature of the hot pressing sintering is 720-750°C, the holding time is 8-10 hours, and the applied pressure is 30-50 MPa. Under the hot pressing conditions, the material can have both excellent compaction performance and suitable specific surface area, further improving the wetting effect of the electrolyte.

[0028] Preferably, in S4, the pressure applied by the cold press forming is 10-20 MPa.

[0029] In the present invention, the protective atmosphere refers to an atmosphere formed by a protective gas, such as nitrogen, helium, or argon.

[0030] The invention also discloses a lithium manganese iron phosphate material, which is prepared by the preparation method.

[0031] The beneficial effects of the present invention are as follows:

[0032] The present invention synthesizes the ternary metal-glycerate precursor of manganese iron M by solvent thermal, which can achieve good uniformity of element distribution in the precursor, thereby improving the uniformity of element distribution in the lithium iron manganese phosphate material, and effectively improving the conductivity and cycle stability of the lithium iron manganese phosphate material; and because the metal-organic composite precursor synthesized by the solvent thermal method has a smaller particle size, the difficulty of the subsequent sand milling process to reduce the particle size is significantly reduced, and the nano-material can be realized in a relatively short time; by combining the means of a primary CVD-like sintering and a secondary hot pressing sintering, the optimal carbon coating effect is achieved on the basis of limited carbon content, and the particle size growth of the lithium iron manganese phosphate material is effectively limited, giving the material good electrical conductivity, and hot pressing sintering can also improve the density of the material, thereby obtaining a good compaction density level. In summary, the preparation process of the present invention can obtain a lithium iron manganese phosphate material with high compaction density, excellent electrical conductivity and cycle stability, and has high production efficiency and industrial application value. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is described in detail below through specific embodiments.

[0034] Example 1

[0035] A method for preparing lithium manganese iron phosphate material comprises the following steps:

[0036] S1. Dissolve 1.76 g of manganese nitrate tetrahydrate, 1.01 g of ferric nitrate nonahydrate and 0.13 g of magnesium nitrate hexahydrate in 150 mL of isopropanol, add 3 g of glycerol and stir at a speed of 200 r / min for 3 h to mix evenly, then carry out solvent thermal reaction at 170 ° C for 18 h in a hydrothermal kettle, centrifuge and wash the obtained precipitate with deionized water and ethanol three times in sequence, and dry it in an oven at 100 ° C for 15 h to obtain a manganese iron magnesium ternary metal-glycerate precursor (titration + elemental analysis shows that the mass fraction of manganese in the precursor is 52.0%, the mass fraction of iron is 18.9%, and the mass fraction of magnesium is 1.6%);

[0037] S2, after mixing 2g of manganese iron magnesium ternary metal-glycerate precursor with 3.11g of ammonium dihydrogen phosphate and 1.05g of lithium carbonate, using anhydrous ethanol as solvent, high-energy ball milling was performed at a speed of 500r / min for 8h, and after the ball milling was completed, the solvent was dried to obtain a lithium manganese iron phosphate precursor;

[0038] S3, placing the lithium manganese iron phosphate precursor in a tubular furnace, introducing a mixed gas of ethane and nitrogen (the volume ratio of ethane to nitrogen is 2:10) at a flow rate of 80 mL / min, and sintering at 550° C. for 5 h to obtain a primary sintering product;

[0039] S4. The primary sintered product is placed in a graphite mold, cold-pressed at a pressure of 20 MPa, and then hot-pressed at 750° C. for 9 hours under an argon atmosphere at a pressure of 30 MPa to obtain a lithium manganese iron phosphate material.

[0040] Example 2

[0041] A method for preparing lithium manganese iron phosphate material comprises the following steps:

[0042] S1. Dissolve 1.76 g of manganese nitrate tetrahydrate, 1.01 g of ferric nitrate nonahydrate and 0.15 g of cobalt nitrate hexahydrate in 150 mL of isopropanol, add 3 g of glycerol and stir at a speed of 300 r / min for 2 h to mix evenly, then perform solvent thermal reaction at 150 ° C for 15 h in a hydrothermal kettle, centrifuge and separate, rinse the obtained precipitate with deionized water and ethanol three times in sequence, and dry it in an oven at 90 ° C for 18 h to obtain a manganese-iron-cobalt ternary metal-glycerate precursor (titration + elemental analysis shows that the mass fraction of manganese in the precursor is 52.0%, the mass fraction of iron is 18.9%, and the mass fraction of cobalt is 4.0%);

[0043] S2, after mixing 2g of manganese iron cobalt ternary metal-glycerate precursor with 3.11g of ammonium dihydrogen phosphate and 1.03g of lithium carbonate, using anhydrous ethanol as solvent, high-energy ball milling was performed at a speed of 400r / min for 6h, and after the ball milling was completed, the solvent was dried to obtain a lithium manganese iron phosphate precursor;

[0044] S3, placing the lithium manganese iron phosphate precursor in a tubular furnace, introducing a mixed gas of methane and nitrogen (the volume ratio of methane to nitrogen is 2:10) at a flow rate of 70 mL / min, and sintering at 600° C. for 6 h to obtain a primary sintering product;

[0045] S4. The primary sintered product is placed in a graphite mold, cold-pressed at a pressure of 15 MPa, and then hot-pressed for 8 hours at 750° C. under an argon atmosphere at a pressure of 50 MPa to obtain a lithium manganese iron phosphate material.

[0046] Example 3

[0047] A method for preparing lithium manganese iron phosphate material comprises the following steps:

[0048] S1. Dissolve 1.38g of manganese nitrate tetrahydrate, 1.62g of ferric nitrate nonahydrate and 0.15g of nickel nitrate hexahydrate in 150mL of isopropanol, add 3g of glycerol and stir at a speed of 200r / min for 3h to mix evenly, then carry out solvent thermal reaction at 180°C for 10h in a hydrothermal kettle, centrifuge and wash the obtained precipitate with deionized water and ethanol three times in sequence, and dry it in an oven at 80°C for 15h to obtain a manganese-iron-nickel ternary metal-glycerate precursor (titration + elemental analysis shows that the mass fraction of manganese in the precursor is 40.9%, the mass fraction of iron is 30.4%, and the mass fraction of nickel is 4.0%);

[0049] S2, after mixing 2g of manganese iron nickel ternary metal-glycerate precursor with 3.12g of ammonium dihydrogen phosphate and 1.05g of lithium carbonate, using anhydrous ethanol as solvent, high-energy ball milling was performed at a speed of 500r / min for 5h, and after the ball milling was completed, the solvent was dried to obtain a lithium manganese iron phosphate precursor;

[0050] S3, placing the lithium manganese iron phosphate precursor in a tube furnace, introducing a mixed gas of propane and nitrogen (the volume ratio of propane to nitrogen is 3:10) at a flow rate of 80 mL / min, and sintering at 600° C. for 6 h to obtain a primary sintering product;

[0051] S4. The primary sintered product is loaded into a graphite mold, cold-pressed at a pressure of 10 MPa, and then hot-pressed at 720° C. for 9 hours under an argon atmosphere at a pressure of 30 MPa to obtain a lithium manganese iron phosphate material.

[0052] Example 4

[0053] A method for preparing lithium manganese iron phosphate material comprises the following steps:

[0054] S1. Dissolve 1.88 g of manganese nitrate tetrahydrate, 0.81 g of ferric nitrate nonahydrate and 0.19 g of aluminum nitrate nonahydrate in 150 mL of isopropanol, add 3 g of glycerol and stir at a speed of 300 r / min for 2 h to mix evenly, then perform a solvothermal reaction in a hydrothermal kettle at 160 ° C for 16 h, centrifuge and separate, rinse the obtained precipitate with deionized water and ethanol three times in sequence, and dry it in an oven at 80 ° C for 13 h to obtain a manganese-iron-aluminum ternary metal-glycerate precursor (titration + elemental analysis shows that the mass fraction of manganese in the precursor is 55.7%, the mass fraction of iron is 15.2%, and the mass fraction of aluminum is 1.8%).

[0055] S2, after mixing 2g of manganese iron aluminum ternary metal-glycerate precursor with 3.12g of ammonium dihydrogen phosphate and 1.03g of lithium carbonate, using anhydrous ethanol as solvent, high-energy ball milling was performed at a speed of 500r / min for 5h, and after the ball milling was completed, the solvent was dried to obtain a manganese iron lithium phosphate precursor;

[0056] S3, placing the lithium manganese iron phosphate precursor in a tubular furnace, introducing a mixed gas of ethane and nitrogen (the volume ratio of ethane to nitrogen is 2:10) at a flow rate of 90 mL / min, and sintering at 550° C. for 5 h to obtain a primary sintering product;

[0057] S4. The primary sintered product is placed in a graphite mold, cold-pressed at a pressure of 15 MPa, and then hot-pressed at 740° C. for 10 hours under an argon atmosphere at a pressure of 35 MPa to obtain a lithium manganese iron phosphate material.

[0058] Example 5

[0059] A method for preparing lithium manganese iron phosphate material comprises the following steps:

[0060] S1. Dissolve 1.51 g of manganese nitrate tetrahydrate, 1.41 g of ferric nitrate nonahydrate and 0.15 g of cobalt nitrate hexahydrate in 150 mL of isopropanol, add 3 g of glycerol and stir at a speed of 250 r / min for 3 h to mix evenly, then carry out solvent thermal reaction at 170 ° C for 13 h in a hydrothermal kettle, centrifuge and separate, rinse the obtained precipitate with deionized water and ethanol three times in sequence, and dry it in an oven at 95 ° C for 17 h to obtain a manganese-iron-cobalt ternary metal-glycerate precursor (titration + elemental analysis shows that the mass fraction of manganese in the precursor is 44.6%, the mass fraction of iron is 26.7%, and the mass fraction of cobalt is 4.0%);

[0061] S2, after mixing 2g of manganese iron cobalt ternary metal-glycerate precursor with 3.11g of ammonium dihydrogen phosphate and 1.06g of lithium carbonate, using anhydrous ethanol as solvent, high-energy ball milling was performed at a speed of 500r / min for 8h, and after the ball milling was completed, the solvent was dried to obtain a lithium manganese iron phosphate precursor;

[0062] S3, placing the lithium manganese iron phosphate precursor in a tube furnace, introducing a mixed gas of ethane and nitrogen (the volume ratio of ethane to nitrogen is 4:10) at a flow rate of 100 mL / min, and sintering at 600° C. for 5 h to obtain a primary sintering product;

[0063] S4. The primary sintered product is loaded into a graphite mold, cold-pressed at a pressure of 18 MPa, and then hot-pressed at 740° C. for 9 hours under an argon atmosphere at a pressure of 50 MPa to obtain a lithium manganese iron phosphate material.

[0064] Example 6

[0065] A method for preparing lithium manganese iron phosphate material comprises the following steps:

[0066] S1. Dissolve 1.38 g of manganese nitrate tetrahydrate, 1.62 g of ferric nitrate nonahydrate and 0.13 g of magnesium nitrate hexahydrate in 150 mL of isopropanol, add 3 g of glycerol and stir at a speed of 300 r / min for 2 h to mix evenly, then carry out solvent thermal reaction at 180 ° C for 15 h in a hydrothermal kettle, centrifuge and rinse the obtained precipitate with deionized water and ethanol three times in sequence, and dry it in an oven at 100 ° C for 15 h to obtain a manganese iron magnesium ternary metal-glycerate precursor (titration + elemental analysis shows that the mass fraction of manganese in the precursor is 40.9%, the mass fraction of iron is 30.4%, and the mass fraction of magnesium is 1.6%);

[0067] S2, after mixing 2g of manganese iron magnesium ternary metal-glycerate precursor with 3.11g of ammonium dihydrogen phosphate and 1.04g of lithium carbonate, using anhydrous ethanol as solvent, high-energy ball milling was performed at a speed of 450r / min for 7h, and after the ball milling was completed, the solvent was dried to remove the solvent to obtain a manganese iron lithium phosphate precursor;

[0068] S3, placing the lithium manganese iron phosphate precursor in a tubular furnace, introducing a mixed gas of ethane and nitrogen (the volume ratio of ethane to nitrogen is 2:10) at a flow rate of 120 mL / min, and sintering at 570° C. for 5 h to obtain a primary sintering product;

[0069] S4. The primary sintered product is loaded into a graphite mold, cold-pressed at a pressure of 20 MPa, and then hot-pressed at 745° C. for 8 hours at a pressure of 40 MPa in an argon atmosphere to obtain a lithium manganese iron phosphate material.

[0070] Example 7

[0071] A method for preparing lithium manganese iron phosphate material comprises the following steps:

[0072] S1. Dissolve 1.76 g of manganese nitrate tetrahydrate, 1.01 g of ferric nitrate nonahydrate and 0.15 g of nickel nitrate hexahydrate in 150 mL of isopropanol, add 3 g of glycerol and stir at a speed of 300 r / min for 2 h to mix evenly, then perform solvent thermal reaction at 170 ° C for 15 h in a hydrothermal kettle, centrifuge, and rinse the obtained precipitate with deionized water and ethanol 5 times in sequence, and dry it in an oven at 90 ° C for 12 h to obtain a manganese-iron-nickel ternary metal-glycerate precursor (titration + elemental analysis shows that the mass fraction of manganese in the precursor is 52.0%, the mass fraction of iron is 18.9%, and the mass fraction of nickel is 4.0%);

[0073] S2, after mixing 2g of manganese iron nickel ternary metal-glycerate precursor with 3.11g of ammonium dihydrogen phosphate and 1.03g of lithium carbonate, using anhydrous ethanol as solvent, high-energy ball milling was performed at a speed of 400r / min for 8h, and after the ball milling was completed, the solvent was dried to obtain a lithium manganese iron phosphate precursor;

[0074] S3, placing the lithium manganese iron phosphate precursor in a tube furnace, introducing a mixed gas of ethane and nitrogen (the volume ratio of ethane to nitrogen is 3:10) at a flow rate of 110 mL / min, and sintering at 600° C. for 6 h to obtain a primary sintering product;

[0075] S4. The primary sintered product is placed in a graphite mold, cold-pressed at a pressure of 20 MPa, and then hot-pressed at 750° C. for 9 hours under an argon atmosphere at a pressure of 30 MPa to obtain a lithium manganese iron phosphate material.

[0076] Comparative Example 1

[0077] A method for preparing lithium manganese iron phosphate material comprises the following steps:

[0078] S1, 4.75g of manganese nitrate tetrahydrate, 2.73g of ferric nitrate nonahydrate, 0.35g of magnesium nitrate hexahydrate, 3.11g of ammonium dihydrogen phosphate, 1.05g of lithium carbonate, and 0.44g of glucose were mixed, and anhydrous ethanol was used as a solvent, and high-energy ball milling was performed at a speed of 500r / min for 10h. After the ball milling, the solvent was dried to remove the solvent to obtain a lithium iron manganese phosphate precursor;

[0079] S2, placing the lithium manganese iron phosphate precursor in a tubular furnace, introducing a mixed gas of ethane and nitrogen (the volume ratio of ethane to nitrogen is 2:10) at a flow rate of 80 mL / min, and sintering at 550° C. for 5 h to obtain a primary sintering product;

[0080] S3. The primary sintered product is placed in a graphite mold, cold-pressed at a pressure of 20 MPa, and then hot-pressed at 750° C. for 9 hours under an argon atmosphere at a pressure of 30 MPa to obtain a lithium manganese iron phosphate material.

[0081] Comparative Example 2

[0082] A method for preparing lithium manganese iron phosphate material comprises the following steps:

[0083] S1. Dissolve 1.76 g of manganese nitrate tetrahydrate, 1.01 g of ferric nitrate nonahydrate and 0.13 g of magnesium nitrate hexahydrate in 150 mL of isopropanol, add 3 g of glycerol and stir at a speed of 200 r / min for 3 h to mix evenly, then carry out solvent thermal reaction at 170 ° C for 18 h in a hydrothermal kettle, centrifuge and wash the obtained precipitate with deionized water and ethanol three times in sequence, and dry it in an oven at 100 ° C for 15 h to obtain a manganese iron magnesium ternary metal-glycerate precursor (titration + elemental analysis shows that the mass fraction of manganese in the precursor is 52.0%, the mass fraction of iron is 18.9%, and the mass fraction of magnesium is 1.6%);

[0084] S2, after mixing 2g of manganese iron magnesium ternary metal-glycerate precursor with 3.11g of ammonium dihydrogen phosphate and 1.05g of lithium carbonate, using anhydrous ethanol as solvent, high-energy ball milling was performed at a speed of 500r / min for 8h, and after the ball milling was completed, the solvent was dried to obtain a lithium manganese iron phosphate precursor;

[0085] S3. The lithium iron manganese phosphate precursor is loaded into a graphite mold, cold-pressed at a pressure of 20 MPa, and then hot-pressed and sintered at 750° C. for 10 hours at a pressure of 30 MPa in an argon atmosphere to obtain the lithium iron manganese phosphate material.

[0086] Comparative Example 3

[0087] A method for preparing lithium manganese iron phosphate material comprises the following steps:

[0088] S1. Dissolve 1.76 g of manganese nitrate tetrahydrate, 1.01 g of ferric nitrate nonahydrate and 0.13 g of magnesium nitrate hexahydrate in 150 mL of isopropanol, add 3 g of glycerol and stir at a speed of 200 r / min for 3 h to mix evenly, then carry out solvent thermal reaction at 170 ° C for 18 h in a hydrothermal kettle, centrifuge and wash the obtained precipitate with deionized water and ethanol three times in sequence, and dry it in an oven at 100 ° C for 15 h to obtain a manganese iron magnesium ternary metal-glycerate precursor (titration + elemental analysis shows that the mass fraction of manganese in the precursor is 52.0%, the mass fraction of iron is 18.9%, and the mass fraction of magnesium is 1.6%);

[0089] S2, after mixing 2g of manganese iron magnesium ternary metal-glycerate precursor with 3.11g of ammonium dihydrogen phosphate and 1.05g of lithium carbonate, using anhydrous ethanol as solvent, high-energy ball milling was performed at a speed of 500r / min for 8h, and after the ball milling was completed, the solvent was dried to obtain a lithium manganese iron phosphate precursor;

[0090] S3, placing the lithium manganese iron phosphate precursor in a tubular furnace, introducing a mixed gas of ethane and nitrogen (the volume ratio of ethane to nitrogen is 2:10) at a flow rate of 80 mL / min, and sintering at 550° C. for 5 h to obtain a sintered product;

[0091] S4. The sintered product is placed in a graphite mold and cold-pressed at a pressure of 20 MPa to obtain a lithium manganese iron phosphate material.

[0092] The lithium iron manganese phosphate materials obtained in the embodiment and the comparative example were ground into powders, and compaction, 0.1C first charge first effect and discharge gram capacity, 1C rate discharge gram capacity were tested. The test method was as follows: the relevant physical and chemical properties and electrochemical properties were tested in accordance with the national standard "Carbon composite lithium iron phosphate positive electrode material for lithium ion batteries" GB / T 30835-2014, wherein the mass ratio of lithium iron manganese phosphate material powder, conductive agent, and binder was 90:5:5, and the charge and discharge voltage range was 2.0-4.5V. The results are shown in Table 1.

[0093] Table 1

[0094]

[0095]

[0096] It can be seen from the above results that the compaction density and electrical properties of the lithium manganese iron phosphate material prepared in the example are significantly better than those in the comparative example.

[0097] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing lithium manganese iron phosphate material, characterized in that: The following steps are involved: S1. preparing a manganese iron M ternary metal-glycerate precursor by a solvothermal synthesis method, wherein M is magnesium, nickel, cobalt or aluminum; S2, mixing the manganese iron M ternary metal-glycerate precursor with a phosphorus source and a lithium source and performing high-energy ball milling to obtain a manganese iron phosphate lithium precursor; S3, placing the lithium iron manganese phosphate precursor in a reaction furnace, introducing a mixed gas of a carbon source gas and a protective gas, and sintering the precursor to obtain a primary sintered product; S4, cold-pressing the primary sintered product, and then hot-pressing and sintering it under a protective atmosphere to obtain the lithium manganese iron phosphate material.

2. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: In the manganese iron M ternary metal-glycerate precursor, the molar ratio of manganese element, iron element and M element is (0.55-0.75): (0.40-0.20): 0.

05.

3. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: The preparation steps of the manganese iron M ternary metal-glycerate precursor include: fully dissolving manganese salt, iron salt and M metal salt in isopropanol, adding glycerol to mix evenly, and then performing a solvent thermal reaction to obtain the precursor.

4. The method for preparing lithium iron manganese phosphate material according to claim 3, characterized in that: The temperature of the solvent thermal reaction is 150-180° C. and the time is 10-20 hours.

5. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: In S2, the ratio of the sum of the molar amounts of manganese, iron and M in the manganese-iron-M ternary metal-glycerate precursor to the molar amount of the phosphorus source and the molar amount of the lithium in the lithium source is 1:1: (1.01-1.05).

6. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: In S2, the rotation speed of the high energy ball mill is 300-500 r / min, and the time is 5-10 h.

7. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: In S3, the flow rate of the mixed gas of the carbon source gas and the protective gas is 70 mL / min to 120 mL / min, and the volume ratio of the carbon source gas to the protective gas is (2 to 4):

10.

8. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: In S3, the sintering temperature is 500-600°C and the holding time is 4-6h.

9. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: In S4, the sintering temperature of the hot pressing sintering is 720-750° C., the holding time is 8-10 hours, and the applied pressure is 30-50 MPa.

10. A lithium manganese iron phosphate material, characterized in that: The method is prepared according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of flaky lithium iron phosphate-carbon composite material

    CN115465848A

  • Preparation method of lithium manganese iron phosphate positive electrode material

    CN116216678A

  • Preparation method of carbon-coated lithium iron manganese phosphate positive electrode material

    CN116544384A

  • Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof

    CN117682493A

  • Lithium manganese iron phosphate composite material and preparation method thereof

    CN117894960A